Implementasi Mesin Penggoreng Mekanis Untuk Meningkatkan Produktivitas Dan Kualitas Kerupuk Amplang Di Ukm Yuan Kartika - Retno Damayanti; Sandra Sandra; Bambang Susilo; Yusuf Hendrawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2020)
Based on the survey, SMEs need technology improvements for the frying process so that the process can be done semi-mechanically. Mechanical fryers have a capacity of 3-4 kg/process, larger than manual which have a capacity of 2 kg of dough/process, so meets the SME production target of 30 kg/day. The frying process takes 15 minutes, faster than the manual frying process for 20 minutes. The level of comfort and safety in the frying process is also better, because the equipment is equipped with a frame so that workers are not affected by heat due to the burner stove heating process. Production results are smooth and meet the production targets, and the quality of the amplang cracker products is the same both before and after the semi-mechanical fryer is applied.